2010
DOI: 10.1029/2009jd012980
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution and variability of formic acid as observed by MIPAS‐ENVISAT

Abstract: Formic acid (HCOOH) vertical profiles have been retrieved from MIPAS‐ENVISAT satellite data in the upper troposphere for the first time. Based on new spectroscopic line‐strength measurements by Vander Auwera et al. (2007) of HCOOH, a retrieval setup was developed and optimized to study its global distribution between 2002 and 2008. A strong seasonality, directly associated to plant growth and corresponding biogenic emissions, is observed and dominates in the middle latitudes of the Northern Hemisphere. Here, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 59 publications
5
48
1
Order By: Relevance
“…Recent work performed with ACE-FTS on quasi-global observations of HCOOH reported an average mixing ratio of about 0.3 ppbv in the free troposphere with hot spots of up to 0.59 ppbv in tropical regions (Abad et al, 2009). Very recent global distributions were also assessed by the MIPAS sounder (Grutter et al, 2010) over a 6 years period. They report seasonal variations that may be associated to biogenic emissions with higher mixing ratios at 8 km during summer (about 100 pptv) than in winter (about 45 pptv).…”
Section: Formic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work performed with ACE-FTS on quasi-global observations of HCOOH reported an average mixing ratio of about 0.3 ppbv in the free troposphere with hot spots of up to 0.59 ppbv in tropical regions (Abad et al, 2009). Very recent global distributions were also assessed by the MIPAS sounder (Grutter et al, 2010) over a 6 years period. They report seasonal variations that may be associated to biogenic emissions with higher mixing ratios at 8 km during summer (about 100 pptv) than in winter (about 45 pptv).…”
Section: Formic Acidmentioning
confidence: 99%
“…Razavi et al: CH 3 OH and HCOOH observations with IASI 2007;Abad et al, 2009). Similarly the observations of the MIPAS limb emission sounder have enabled mapping upper tropospheric distributions of several organic species such as PAN (Glatthor et al, 2007;, acetone as well as HCN and C 2 H 6 (Glatthor et al, 2009); very recently global distributions of formic acid have also been gathered and analyzed (Grutter et al, 2010). The possibility of probing these VOCs lower in the atmosphere using nadir infrared sounders was suggested based on local observations, both by TES (Beer et al, 2008) and IASI , in the latter case in large biomass burning plumes.…”
mentioning
confidence: 99%
“…The Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) limb emission instrument mapped upper-tropospheric distributions of several species, such as HCN and C 2 H 6 (Glatthor et al, 2009). It also measured HCOOH at a 10 km altitude between 70 and 90 • N (Grutter et al, 2010). The Atmospheric Chemistry Experiment (ACE) is able to monitor all seven species derived in this study, with periodic sampling over the Arctic.…”
Section: Introductionmentioning
confidence: 99%
“…The limb-viewing Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE-FTS) observed formic acid in young and aged biomass burning plumes in the upper troposphere and derived emission ratios for formic acid to CO [30,31]. Similarly, Grutter et al used the limb-viewing Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) to retrieve global distributions of formic acid in the upper troposphere and stratosphere [32]. Razavi et al presented global distributions of formic acid retrieved using the nadir-viewing IASI instrument and showed that the retrieved formic acid is correlated with CO during the burning season in Brazil, the Congo, and Southeast Asia [33].…”
Section: Introductionmentioning
confidence: 99%